Optimal Deployment of Camera Mounted UAVs Performing Search - Marina D’Souza, Jeane; Suresh Rao, Siddhartha; R. Guruprasad, K (International Journal of Engineering and Technology, 2018)
In this paper we address a problem of optimal deployment of camera mounted UAVs for a multi-robot search application. Here   multiple UAVs carrying downward facing cameras are required to look for targets of interest in a search area. The lack of information about the presence or absence of targets is modeled as an uncertainty density distribution over the search area and this uncertainty is reduced as the information is gathered using the onboard cameras. The UAVs are required to get deployed so as to maximize the uncertainty reduction. We provide a model for search effectiveness of the camera and use it to formulate a strategy for optimal deployment of UAVs. It is shown that a centroidal Voronoi configuration, where each UAV (camera) is located at the centroid of the corresponding Voronoi cell is an optimal deployment. We provide simulation results to demonstrate that the proposed optimal deployment strategy successfully      deploys the UAVs into centroidal Voronoi configuration, which maximizes the uncertainty reduction using cameras as search sensors.